A Free Streaming Contact Preserving Scheme for the M1 Model (Advances in Applied Mathematics and Mechanics, 2018)
The present work concerns the numerical approximation of the $M_1$ model for radiative transfer. The main purpose is to introduce an accurate finitevolume method according to the nonlinear system of conservation laws that governsthis model. We propose to derive an HLLC method which preserves the stationarycontact waves. To supplement this essential property, the method is provedto be robust and to preserve the physical admissible states. Next, a relevant asymptoticpreserving correction is proposed in order to obtain a method which is ableto deal with all the physical regimes. The relevance of the numerical procedure isexhibited thanks to numerical simulations of physical interest.